The Performance of Undershot Water Turbine Combined With Spiral Tube Pump On Empowerment of Energy Resources Local Contiguous Small River - Asral, Asral; Akbar, Musthafa; Syafri, Syafri (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2017)
Hundreds of kilometers of irrigation canals are generally contiguous the village has not been maximally helpful as well most of damaged. Basically, in the water flow available an amount of energy could be harnessed as a renewable energy resources. Shortage of water and electricity supplies are the major issues encountered by the villager. Irrigation canals have head differences including low coupled lies in lowland areas. Picohydro electric generation, undershot-type water turbine suited for low high head applications in attemp to gain the electricity. To move the water, spiral tube pump mounted on the turbine can be installed simultaneously on generating systems. The turbine developed has an outer diameter of 2 m with 18 pieces of straight blade prepared from the material of aluminum. On the side of the turbine wall embeded the spiral tube pump with 5 coils was designed to operate concurrently with electrical generation. The height of water resources varied by controlling the opening of sluice gates to find out the potential. Throughout study the maximum electric voltage achievements was 125 volt. At the same time, the pump discharged the water with 9 liters per menit. These results provide sufficient supply of freshwater and electrical power for a family at contiguous area.